Historical Persepective: Gavriil Ilizarov, MD - Iobst, Christopher; Alexander Cherkashin; Robert Wigginton (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Gavriil Ilizarov (1921-1992) would have celebrated his 100th birthday in 2021. His contributions to the field of orthopaedic surgery are simply extraordinary. While he is most famous for the circular external fixator system that bears his name, his principles of distraction osteogenesis revolutionized the field of limb lengthening and reconstruction. Despite having no formal education in orthopaedics, he developed a method that became so successful that an 800-bed orthopaedic hospital was built for him in Kurgan, Siberia. The Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics became the largest orthopaedic clinic in the world.